Mechanochemical properties of brain clathrin: interactions with actin and alpha-actinin and polymerization into basketlike structures or filaments. - Schook, W (1979)
Two molar urea (pH 7.5) and column chromatography on Sepharose 4B were used to separate clathrin (coat protein) from the membrane of coated vesicles from bovine brain. Lytron (polystyrene) particles were used for study of the interaction of clathrin with contractile proteins. Muscle G-actin, F-actin, and alpha-actinin were bound by clathrin-coated Lytron particles, while no interaction was found when muscle tropomyosin and serum albumin were tested. Clathrin molecules dispersed in a solution of 20 mM Tris-HCl (pH 7.5) were found to be elongated. When the pH was adjusted from 7.5 to 6.5, clathrin molecules associated into basketlike or cage structures similar in size and shape to those observed in enriched preparations of coated vesicles. Below pH 6.0, cages or baskets became amorphous aggregates. Raising the pH from 6.5 to 8.0, addition of 5-10 mM ATP or EDTA, or addition of 200 mM KCl resulted in the dissassembly of baskets and the formation of filamentous arrays of various widths. Because of clathrin's biochemical and biophysical properties, its interaction with contractile proteins, and its presence in the membrane of vesicles of various cell types, we classified clathrin in the group of mechanochemical proteins.